The Effect of Endorphin Massage on Back Pain Intensity in Pregnant and Laboring Women: A Literature Review - Yeni Septia Ningsi; Nova Elok Mardliyana (Jurnal Keperawatan Olahraga, 2025)
Background: Endorphin massage is a gentle massage technique aimed at stimulating the body to release endorphins. It has been shown to be effective in reducing pain intensity. Objective: To evaluate the effect of endorphin massage on back pain intensity in pregnant and laboring women based on research findings. Methods: A literature review was conducted by collecting credible research articles from databases such as Scopus, PubMed, Google Scholar, and SINTA. Articles that met the predetermined inclusion criteria were then subjected to data extraction. Results: Following data extraction from 110 articles, 5 articles were deemed eligible. Two of the studies involved endorphin massage combined with other interventions, while the remaining three involved endorphin massage alone. Discussion: Endorphin massage has been proven effective in reducing back pain in pregnant and laboring women. Conclusion: Although the preliminary findings are promising, further research is necessary to confirm the effectiveness of this intervention more comprehensively. It is recommended to use a Randomized Controlled Trial (RCT) design with a more homogeneous population and diverse study locations across various countries to enhance the validity and generalizability of the findings.